MEKANISME KOPING UNTUK MENGATASI NYERI PERSALINAN KALA 1 - Wahyu purwaningsih; Annisa Andriyani (Jurnal Infokes, 2014)
Introduction : Childbirth is an event filled with stress on most women giving birth that causes increased pain , fear and anxiety.Coping mechanisms used different birth mothers - both very depending multigravida, primigravida or the factors that influence maternal coping mechanism in the active phase. Objective: To describe the characteristics primigravida and multigravida , coping mechanisms for pain multigravida and primigravida, and know the difference in the coping mechanisms used primigravida and multigravid to cope with labor pain. Methods: univariate and bivariate analyzes t-test.Result : Characteristics at least primigravida dominant for ages 20-34 years (85.7%) , secondary education (57.1%) , work as employees (57.1%) , Assistance during childbirth is the husband (57.1%) . Characteristics of the most dominant multigravid mother for ages 20-34 years (79.3%) , birth spacing 2-5 years (55.2%) , secondary education (75.9%) , work as housewives (41.44%) , Assistance during childbirth is the husband (69%) . Coping mechanisms are maladaptive in primigravida (71.4 %) , while the mechanism of adaptive coping in mothers multigravida (55.2%) and there are differences in coping mechanisms used in primigravida and multigravida mothers , seen from the mean difference for the multi primigravida 13 and 16.24 .Conclusion ; coping mechanisms used in primigravida first stage of labor pain is maladaptive whereas the adaptive multigravida. Keywords: Coping Mechanisms , Primigravida, Multigravida, Delivery